An exploratory study on cortical hemodynamics and handgrip strength phenotypes in long-term hospitalized patients with stable schizophrenia - Yanping Feng; Yilin Wang; Binyou Wang (PLoS ONE, 2026)
Objective This exploratory study aims to investigate the relationship between handgrip strength (HGS) phenotypes and cortical hemodynamics in long-term hospitalized patients with stable schizophrenia, and to evaluate whether HGS could serve as a potential indicator of neurocognitive function in this population. Methods In this cross-sectional study, 96 patients with stable schizophrenia were enrolled. HGS was assessed using a calibrated dynamometer. Cortical hemodynamic responses during a Verbal Fluency Task (VFT) were measured using functional near-infrared spectroscopy (fNIRS), with metrics derived from both oxygenated hemoglobin (Oxy-Hb) and total hemoglobin (Total-Hb) signals, including the S-integral, T-centroid, and K-activation. Statistical analyses comprised Spearman correlation analysis, univariate linear regression, and general linear models with post hoc comparisons. Results Among the participants, 40.60% (39/96) were male and 59.40% (57/96) were female, with a median (P25, P75) age of 52 (42, 56) years. Univariate linear regression revealed a significant positive association between HGS asymmetry and frontal lobe S-integral values (Oxy-Hb: β = 65.650, 95% CI: 18.488–112.812, P = 0.007; Total-Hb: β = 64.878, 95% CI: 19.360–110.395, P = 0.006). However, after adjusting for potential confounders, general linear models revealed no significant differences in frontal S-integral values across HGS asymmetry subgroups, regardless of whether asymmetry was classified by percentage-based thresholds or dominance type (all Bonferroni-adjusted P > 0.05). Conclusion In this exploratory study, HGS asymmetry was associated with frontal S-integral values unadjusted; however, after adjusting for confounders and multiple comparisons, no significant independent association remained. HGS phenotypes cannot be considered reliable or simple surrogate markers of neurocognitive activity in this population, underscoring the substantial influence of confounding neurophysiological factors in schizophrenia.